ANALISIS POSISI TAWAR MASYARAKAT DALAM PELAYANAN KESEHATAN PUSKESMAS DI KOTA SERANG - Agus Sjafari; Arenawati Arenawati; Yeni Widyastuti (Universitas Sultan Ageng Tirtayasa, 2015)
One of the obligatory functions of local government is in the health sector.Health is one of the capital construction. With good health, people can work, childrencan concentrate on studying, so it will be good productivity as well. Therefore healthcan be measured by the welfare of society. This study aims to determine the extent oftheir bargaining position in health care clinics in the city of Serang. This research isquantitative descriptive. The study population was people which have used communityhealth center services (Puskesmas). The sample in this study were : Puskesmas DTPSerang, Puskesmas Singandaru, Puskesmas Cipocok and Puskesmas Kalodran. Thenumber of respondents of this study were 100 people .. The results showed that the levelof their bargaining position in health care clinics in the city of Serang amounted to 7.61with very good category. Suggestion of this research are health centers provide adocument that contains the rights and obligations of providers and users of services,minimum service standards to inform the user of health care and the clinic should bequick to respond if there is a complaint.